PROGRAM KELUARGA HARAPAN (PKH) DI KELURAHAN BIDARA CINA, JAKARTA TIMUR: FAKTOR PENDORONG DAN PENGHAMBAT IMPLEMENTASI - Kurnia Fajri, Amelia; Purnaweni, Hartuti; Rina Herawati, Augustin (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
Based on Permensos Number 1 of 2018 concerning Family Hope Program (PKH), PKH is a program to provide conditional social assistance by the government to poor or vulnerable families or individuals registered in the DTKS (Social Welfare Integrated Data). Since 2007 the PKH has received positive aspirations. However, until now the decline in poverty rate still results in a low poverty reduction rate indicator and the self-graduation process of program participants is still low which indicates that this program is only running on the spot. This article aims to analyze the implementation of PKH policies in Bidara Cina Village using qualitative descriptive methods, data collection is carried out by interviewing, observation, and documentation. The research results show that the implementation of PKH policy in Bidara Cina is not good enough, because there are still several problems. In addition, although this program has been implemented in accordance with the goal of Permensos Number 1 of 2018, it has not been fully implemented in accordance with the standards stated in the regulation. This is because the purpose of the program is not fully understood by the program participants. The obstacle to the implementation of the Family Hope Program is resources, namely the insufficient number of program assistants. Meanwhile, the supporting factors are communication that has been done well, disposition of policy implementers with good performance and work spirit, and clear and tiered bureaucratic structure.